THE UNIQUE DEVELOPMENT OF SPECIAL EDUCATION IN FRANCE - Rakhimova Munirakhan Ilhomovna; Dinora Mamatova (Galaxy International Interdisciplinary Research Journal, 2023)
This article aims to shed light on the unique role and importance of the development of special education in France in the education of children with disabilities.